2015
DOI: 10.1021/jacs.5b04879
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Nitriles to Primary Amines Catalyzed by a Cobalt Pincer Complex

Abstract: The catalytic hydrogenation of nitriles to primary amines represents an atom-efficient and environmentally benign reduction methodology in organic chemistry. This has been accomplished in recent years mainly with precious-metal-based catalysts, with a single exception. Here we report the first homogeneous Co-catalyzed hydrogenation of nitriles to primary amines. Several (hetero)aromatic, benzylic, and aliphatic nitriles undergo hydrogenation to the corresponding primary amines in good to excellent yields under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
131
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(135 citation statements)
references
References 56 publications
3
131
0
1
Order By: Relevance
“…For example, in 2012 Hanson and co‐workers have reported a new aliphatic PNP pincer Co II complex for the hydrogenation of olefins, ketones, aldehydes, and imines . Later, Milstein and co‐workers have developed another Co II system with pyridine‐based PNN pincer ligand for the hydrogenation of esters and nitriles . Very recently, the group of Fout has showed that Co I complexes with monoanionic bis(carbene) ligands can also promote olefin hydrogenation through a Co I /Co III redox cycle (Figure ) …”
Section: Figurementioning
confidence: 99%
“…For example, in 2012 Hanson and co‐workers have reported a new aliphatic PNP pincer Co II complex for the hydrogenation of olefins, ketones, aldehydes, and imines . Later, Milstein and co‐workers have developed another Co II system with pyridine‐based PNN pincer ligand for the hydrogenation of esters and nitriles . Very recently, the group of Fout has showed that Co I complexes with monoanionic bis(carbene) ligands can also promote olefin hydrogenation through a Co I /Co III redox cycle (Figure ) …”
Section: Figurementioning
confidence: 99%
“…[21,22] The futureo fl iquid organich ydrogen carriers (LOHC) depends on ar eversiblec hemical reactionb ased on the release and uptake of hydrogen. [30][31][32][33][34][35] Nitriles are versatile intermediates in organic synthesis owing to their direct conversion into av arietyo ff unctionalg roups.C onventional organic procedures requiren ucleophilic displacemento fs uitable leaving groups producing stoichiometrica mounts of waste and with limited selectivity. [28] The acceptorless dehydrogenation of primary amines generates the corresponding nitrile and two moles of hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt compounds, and here especially cobalt pincer type complexes, have been developed for a number of catalytic transformations such as polymerization, bond‐forming reactions, hydrogenations, transfer hydrogenations, hydrosilylations/hydroborations or N 2 activation . Although cobalt‐based reductions of ketones,, aldehydes , nitriles, or alkenes,,, have been studied, until now, hydrogenation of carboxylic acid esters in the presence of this metal has been scarcely examined…”
Section: Figurementioning
confidence: 99%